Variación morfométrica en el murciélago Sturnira Magna (Chiroptera: Phyllostomidae) Variación morfométrica en el murciélago Sturnira Magna (Chiroptera: Phyllostomidae) - Tamsitt J. R.; Valdivieso Darío (Caldasia)
Evaluamos variación sexual y geográfica en el murciélago neotropical Sturnira magna (Phyllostomidae) por medio de análisis estadístico univariado y multivariado de medidas craneales, mandibulares y corporales. El dimorfismo sexual es significante. Los machos son más grandes que las hembras.  No encontramos variación geográfica en tamaño y la especie presenta una homogeneidad fenética notable en su extensión geográfica desde el sur de Colombia hasta el norte de Bolivia. Se anota que los ejemplares del Perú Andino son ligeramente más pequeños que los de la Cuenca Amazónica por análisis univariado. El tamaño no está correlacionado ni con factores climáticos (temperatura anual media, precipitación anual media, evapotranspiración relativa), ni con factores geográficos (elevación, latitud relativa). We assessed sexual and geographic variation in the neotropical bat Sturnira maqna (Phyllostomidae) from univariate and multivariate statistical analyses of cranial, mandibular, and body measurements of specimens representative of the geographic range of the species. Sexual dimorphism is significant, and males are larger than females. Cramial, condiloincisive, and mandibular lengths, width across lower canines, length of third and fourth metacarpals, and length of the first phalanx of the third and fifth digits were the main determinants in discriminant analysis to separate the sexes. Analysis of geographic variation in size revealed no distinct geographic pattern. Size was not correlated with mean annual temperature, mean annual precipitation, or potential evapotranspiration, nor with elevation or relative latitude. Cranial, condiloincisive, palatal, mandibular, and upper-toothrow lengths in males and cranial length, mastoid width, and length of the upper toothrow in females were the main determinants in principal component analysis. A notable phentic homogenity in size was found in specimens from the Amazon Basin and from the Amazonian slope of the Andean Cordillera in Perú. Univariate analyses however revealed that in certain measurements S. magna are somewhat smaller in Andean Perú than elsewhere.